Synthesis and investigation of the geometric characteristics of titanium dioxide nanotubes - Serikov, T.M.; Ibrayev, N.Kh.; Gladkova, V.K. (IOP Conf. Series: Materials Science and Engineering, 2015)
The nanotubes of titanium dioxide were produced by electrochemical anodization of metallic titanium in a fluorine-containing electrolyte. The influence of the electrolyte composition, voltage and time of anodization on the geometric characteristics of the synthesized nanotubes was investigated.
Keywords: titanium dioxide nanotubes; geometric characteristics; Synthesis; investigation